Phylogenetic relationship of plastid large single copy genome and potential of ginsenoside compounds from Panax in Alzheimer disease - Kinasih, Anggiresti; Ahmar, Rasyidah Fauzia; Fatmawati, Dwi Retno; Rivaldi, Muhammad; Suhaemi, Emi; Saputra, Novanda Eka; Haniyyah, Hernanda Afra (Universitas Islam Negeri Mataram, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the most prevalent cause of dementia, marked by cognitive decline and memory loss. Current treatments are largely symptomatic and do not halt disease progression, underscoring the urgent need for novel therapeutics. Natural products, such as Panax notoginseng, offer promising alternatives due to their structural diversity and multi-target potential. This study investigates the therapeutic potential of 125 terpenoid compounds identified from P. notoginseng, focusing on their relevance to AD. Eight ginsenosides demonstrated notable neuroprotective effects, including improvements in memory and cognitive function. Among them, Ginsenoside Rb1 and Notoginsenoside R1 exhibited low predicted toxicity via oral and intraperitoneal routes, indicating favorable safety profiles. Target prediction and molecular docking suggest these compounds interact with G protein-coupled receptors implicated in cognition and neuroprotection, such as dopaminergic, serotonergic, muscarinic, and adrenergic receptors. However, their deviation from Lipinski’s Rule of Five may limit oral bioavailability. To address this, nanotechnology-based delivery systems are proposed to enhance solubility, permeability, and drug-likeness. These findings support the continued exploration of P. notoginseng ginsenosides as potential anti-dementia agents and highlight nanotechnology's role in overcoming pharmacokinetic limitations